O tráfico e a caça de animais silvestres no Tocantins e suas implicações para a conservação da biodiversidade regional - Iansen, Yohana (Universidade Federal do Tocantins, 2020)
Hunting and animal trafficking are activities rooted in Brazilian culture, being some of the main causes of depletion of species populations, just behind the loss of habitat for deforestation and burning. The state of Tocantins, shares two of the most biodiverse biomes on the planet (cerrado and Amazon), a fact that makes it a target for poaching and wildlife trafficking, however, the state does not yet have a compilation of data on the occurrence of such crimes. Environmental issues. In addition to the knowledge gap that the state represents, inspection is scarce; the inspectors' lack of preparation; the lack of allocation of funds and socio-environmental education; they are factors that stimulate the continuation of illegal activities involving fauna. The objective of this work was to make a diagnosis of hunting and trafficking in the state of Tocantins. The diagnosis was made through the analysis of infraction notices drawn up by the responsible environmental agencies between the years 2000 and 2018 and included in the Integrated Environmental Management System (SIGA), in addition to assess the implications of these activities for the conservation of regional biodiversity. The results obtained indicated that hunting and trafficking activities are practiced in all regions of the state, with emphasis on the municipality of Alvorada in the southern region. The prevalence of subsistence hunting for mammals and reptiles and trafficking for avifauna was observed.